Islamic Boarding School Management in Instilling Religious Moderation - Zulhimma Zulhimma; Zulhammi Zulhammi; Suheri Sahputra Rangkuti (Pascasarjana Universitas KH. Abdul Chalim, 2026)
Islamic boarding schools have a significant role in shaping the religious perspective of the young generation of Muslims. In the midst of contemporary socio-political dynamics, this role is increasingly crucial, especially when religious discourse is often colored by polarization, exclusivism, and symptoms of intolerance and radicalism that target young people, including students. This study aims to describe and analyze the management approach of the Al-Ansor Padangsidimpuan Islamic Boarding School in instilling religious moderation among students. Religious moderation is an urgency in the context of contemporary Islamic education in response to the increasing symptoms of intolerance and radicalism. This study uses a qualitative, descriptive approach, collecting data through observation, interviews, and documentation. The results of the study show that pesantren management includes planning the goals and policy directions of pesantren related to religious moderation, active involvement of teachers and caregivers, contextual learning activities, inclusive da’wah, and dialogue between students, as the main instruments for internalizing the values of moderation. In addition, pesantren implement social and cultural control mechanisms based on example and habituation of values in daily life. This study recommends replicating these management models in other Islamic educational institutions to strengthen grassroots religious moderation.